Vegan and Animal Meal Composition and Timing Influence Glucose and Lipid Related Postprandial Metabolic Profiles. Issue 5 (21st February 2019) - Draper, Colleen Fogarty; Tini, Giulia; Vassallo, Irene; Godin, Jean Philippe; Su, MingMing; Jia, Wei; Beaumont, Maurice; Moco, Sofia; Martin, Francois‐Pierre
Abstract : Scope: Flexitarian dieting is increasingly associated with health benefits. The study of postprandial metabolic response to vegan and animal diets is essential to decipher how specific diet components may mediate metabolic changes. Methods and results: A randomized, crossover, controlled vegan versus animal diet challenge is conducted on 21 healthy participants. Postprandial metabolic measurements are conducted at seven timepoints. Area under the curve analysis of the vegan diet response demonstrates higher glucose (EE 0.35), insulin (EE 0.38), triglycerides (EE 0.72), and nine amino acids at breakfast (EE 4.72–209.32); and six lower health‐promoting fatty acids at lunch (EE −0.1035 to −0.13) ( p < 0.05). Conclusions: Glycemic and lipid parameters vary irrespective of diet type, demonstrating that vegan and animal meals contain health‐promoting and suboptimal nutrient combinations. The vegan breakfast produces the same pattern of elevated branched chain amino acids, insulin, and glucose as the animal diet from the fasting results, reflecting the low protein load in the animal and the higher branched‐chain amino acid load of the vegan breakfast. Liberalization of the vegan menu to vegetarian and the animal menu to a Nordic‐based diet can result in optimal metabolic signatures for both flexitarian diet strategies in future research. Abstract : Flexitarian dieting is increasingly associated with health benefits. The study of postprandial metabolic response to vegan and animal diets helps decipher how specific diet components may mediate metabolic changes. This randomized, crossover, controlled vegan versus animal diet challenge reveals that both vegan and animal meal plans contain health promoting and suboptimal nutrient combinations.